Efficacy of Keyhole Approach to Carpal Tunnel Syndrome under Ambulatory Strategy - Ramos-Zúñiga, Rodrigo (Neurol Res Int, 2017)
The carpal tunnel syndrome is one of the most common entrapment neuropathies found in humans. Currently, the gold standard is surgical treatment using different modalities. The minimally invasive strategy with high resolution capacity and less morbidity is still a challenge. Methods. Prospective nonrandomised clinical trial in which a minimally invasive microsurgical approach was used following the keyhole principle in 55 consecutive patients and 65 hands under local anesthesia and ambulatory strategy. They were evaluated with stringent inclusion criteria with the Levine severity and functional status scale and with a 2-year follow-up. Results. 90% showed immediate improvement dropping to grades 1-2 in all items of the scale referring to pain and numbness. 97% reported improvement, as of the first month, and 3% reported persistence of symptoms, although at a lesser degree and with no functional limitation. No incidents were identified during the procedure and 98% of patients were discharged within an hour after the surgical procedure. Conclusions. The microsurgical approach described following the keyhole principle is a treatment option that, under local anesthesia and ambulatory management, may represent an alternative strategy of an effective treatment reducing the morbidity. This trial is registered with Clinical Trials Protocol Identifier NCT03062722.